Quality at Time of Purchase of Dried Milk Products Commercially Packaged in Reduced Oxygen Atmosphere - Lloyd, M.A.; Zou, J.; Farnsworth, H.; Ogden, L.V.; Pike, O.A. (Journal of dairy science, 2004)
Nonfat dry milk (NDM) and powdered whey beverages are available at the retail level, packaged in No. 10 cans in a reduced oxygen atmosphere to prolong shelf life. The objective of this research was to determine the sensory and nutritional quality of these dried milk products at the time of purchase. In the 10 brands tested, wide variation existed in headspace oxygen, can seam quality, sensory quality, and vitamin A (with 6 of 10 brands entirely lacking the vitamin). Manufacturers of dried milk products packaged in cans for long-term storage need to give careful attention to can seam quality, product labeling, and vitamin fortification. Consumers would be well advised to evaluate several brands of dried milk products prior to large quantity purchases.